Sports heroes, fallen idols - Teitelbaum, Stanley H. (University of Nebraska Press, 2005)
On the court and on the field, they are the world's winners, exhibiting a natural grace and prowess their adoring fans can only dream about. Yet so often, when off the field, our sports heroes lose: their perspective, their balance, their place. In a work as timely as the latest fracas on the basketball court or the most recent drug-induced scandal in the dugout, Stanley H. Teitelbaum looks into the circumstances behind so many star athletes' precipitous fall from grace. Why, he asks, do these sports heroes who seem to have it all also seem, increasingly, to have a superhuman proclivity for se.